PENDIDIKAN KELUARGA DALAM AL-QURAN - Muhammad Yusran; Muhammad Nur Effendi (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2024)
Family is the smallest element of a country. If the family is good, the country will be good, but if the family is broken, the government will also be broken. A good family is one whose components function well, knowing their respective roles and functions. The smallest family consists of a father, mother and child. If the three components of the family know their roles and functions, then the family will become a sakinah mawaddah warahmah family. This study aims to find data conclusions about how family education in the Quran, which includes the purpose of family education in the Quran, family education materials in the Quran, and family education methods in the Quran. This research is a literature research with a qualitative approach. The primary data sources in this research are the Quran and the results of thoughts derived from the interpretation of the Quran. The collected data is then analysed by content analysis. The purpose of family education is in accordance with the objectives of Islamic education in the Quran. The material of family education is about justice, morals, intellectuals, and worship. While the methods of family education are exemplary, habituation methods, methods and Targhiib and Tarhiib (punishment and reward)